1980
DOI: 10.2307/2529985
|View full text |Cite
|
Sign up to set email alerts
|

On Modelling Microbial Infections

Abstract: Several models for the course of microbial infections during the incubation period are examined. Each model fits sore throat incubation data very well. Together with the lack of precision of the resulting parameter estimates, this suggests that incubation data alone are insufficient for elucidating the finer details of the development of diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The success with which these data allowed us to detect effects of demographic stochasticity and a dynamic immune system suggests that response times do indeed provide substantial information about within-host pathogen growth, despite the Morgan and Watts (1980) argument that responsetime data are insufficient for model comparison. A key difference between their work and ours, however, is that we took a Bayesian approach to estimate our model parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success with which these data allowed us to detect effects of demographic stochasticity and a dynamic immune system suggests that response times do indeed provide substantial information about within-host pathogen growth, despite the Morgan and Watts (1980) argument that responsetime data are insufficient for model comparison. A key difference between their work and ours, however, is that we took a Bayesian approach to estimate our model parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because estimating some of the model parameters from response-time data alone is very difficult (Morgan and Watts 1980). For example, unreasonably low estimates of the median threshold population size N can produce reasonable speeds of kill if the estimate of the virus growth rate parameter f is also very low.…”
Section: Bayesian Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as far as we continue to rely on observed frequencies and arbitrarily chosen specific distributions, it is essential that comparisons using different distributions are made; any assumptions should be explicitly evaluated by means of significance tests and visual assessments. Second, the biological validity of assuming specific distributions for the incubation period remains an open question [100,101], and thus, further information is needed. For example, within-host dynamics would help clarify disease onset mechanisms in the most explicit way [102].…”
Section: A Further Critique Of the Lognormal Assumptionmentioning
confidence: 99%
“…Morgan and Watts tested the Williams model against data reported by Sartwell and found that there was poor identifiability of parameters, although the model provided good fit. In particular, the time to effect data only provided good estimates of the difference between birth and death rates, μ – λ, and also the estimates of the threshold burden to effect (N), appeared implausible.…”
Section: Experimental Frameworkmentioning
confidence: 99%